Dishevelled Paralogs in Vertebrate Development: Redundant or Distinct? - Gentzel, Marc; Schambony, Alexandra (Frontiers in Cell and Developmental Biology, 2017)
Dishevelled (DVL) proteins are highly conserved in the animal kingdom and are important key players in β-Catenin-dependent and -independent Wnt signaling pathways. Vertebrate genomes typically comprise three DVL genes, DVL1, DVL2 and DVL3. Expression patterns and developmental functions of the three vertebrate DVL proteins however, are only partially redundant in any given species. Moreover, expression and function of DVL isoforms have diverged between different vertebrate species. All DVL proteins share basic functionality in Wnt signal transduction. Additional, paralog-specific interactions and functions combined with context-dependent availability of DVL isoforms may play a central role in defining Wnt signaling specificity and add selectivity towards distinct downstream pathways. In this review, we recapitulate briefly cellular functions of DVL paralogs, their role in vertebrate embryonic development and congenital disease.